To find the solution to the system of equations, we need to identify the point at which the two equations intersect. Let’s look at the y-values from the table for each corresponding x-value:
For the equation \( y = 2x - 5 \):
- When \( x = 0 \), \( y = -5 \)
- When \( x = 1 \), \( y = -3 \)
- When \( x = 2 \), \( y = -1 \)
- When \( x = 3 \), \( y = 1 \)
For the equation \( y = x - 3 \):
- When \( x = 0 \), \( y = -3 \)
- When \( x = 1 \), \( y = -2 \)
- When \( x = 2 \), \( y = -1 \)
- When \( x = 3 \), \( y = 0 \)
Next, we find a common (x, y) pair from both equations. From the table:
- At \( x = 2 \), the \( y \) value for both equations is \( -1 \).
- At \( x = 3 \), the \( y \) value for \( y = 2x - 5 \) is \( 1 \) and for \( y = x - 3 \) is \( 0 \).
The only solution that satisfies both equations is when \( x = 2 \) and \( y = -1 \).
Thus, the solution for the system of equations is \( (2, -1) \).
The correct response is:
(2,−1)